2018
DOI: 10.1080/17461391.2018.1496146
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of urinary incontinence in high‐impact sports athletes and their association with knowledge, attitude and practice about this dysfunction

Abstract: There is a high prevalence of UI yet low levels of adequate knowledge and practice regarding the occurrence of UI in sports, with sports practice time over 8 years and dyspareunia factors predisposing female athletes to UI by 2.7 and 3 times, respectively. Athletes with adequate knowledge were 57% less likely to develop UI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
62
3
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(87 citation statements)
references
References 44 publications
8
62
3
14
Order By: Relevance
“…32 On the other hand, Yi et al 13 found that 24% of tri-athletes had at least one arm of the female athlete triad, but the athletic triad was not associated with symptoms of any pelvic floor disorders, for example, UI. Our results did not confirm other findings from other sports where low BMI 12,29 and length of participation in sport/hours of training 15,18,[33][34][35][36][37][38][39][40][41][42][43] were significant risk factors. This may be explained by the high training load and low BMI in all the rhythmic gymnasts.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…32 On the other hand, Yi et al 13 found that 24% of tri-athletes had at least one arm of the female athlete triad, but the athletic triad was not associated with symptoms of any pelvic floor disorders, for example, UI. Our results did not confirm other findings from other sports where low BMI 12,29 and length of participation in sport/hours of training 15,18,[33][34][35][36][37][38][39][40][41][42][43] were significant risk factors. This may be explained by the high training load and low BMI in all the rhythmic gymnasts.…”
Section: Discussioncontrasting
confidence: 99%
“…As expected, only few of these young rhythmic gymnasts had heard about the pelvic floor or knew how to train the PFM. Low level of knowledge and adequate practice to treat UI has been found in another study of athletes, 18 but is also common in the non-athlete, young, nulliparous population. Neels et al 38 found that nulliparous women aged 18-27 years rated their general knowledge about the pelvic floor as a mean of 2.4 (SD 2.01) on a VAS scale from 0 to 10.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The reduction of UI during exercise after starting the quarantine was statistically signi cant and the reasons appointed by the respondents were the interruption of double under exercises and the reduction in the intensity of the training. Double under is the CrossFit movement that most frequently increases the intra-abdominal pressure (429 cm H2O), this value being one of the highest ever attributed to any sporting gesture [5]. In a previous study performed from our group [6], it was the exercise mostly associated with UI.…”
Section: Discussionmentioning
confidence: 83%
“…High performance and high impact sports, such as acrobatic trampoline, weightlifting and long-distance running, may cause a two-fold to increase the odds for UI in young athletes [2,3]. In middle-aged women, losing urine signi cantly limits physical activity [4,5].…”
Section: Introductionmentioning
confidence: 99%